INTENSI PENGGUNA LAYANAN PESAN ANTAR MAKANAN SECARA DARING: STUDI KASUS PENGGUNA GOFOOD, GRABFOOD, DAN SHOPEEFOOD - Muhammad Rifky, (2023)
This research aims to examine the impact of perceived convenience, service quality, and transaction security on consumers' attitudes and intentions to use online food delivery services in Indonesia. Based on an expanded model of technology acceptance that includes perceived convenience, service quality, and transaction security, along with their influences on consumer attitudes as a mediator and the dependent variable of consumer usage intentions for online food delivery services. In this study, the researchers collected data from 100 participants who use online food delivery services in Indonesia and analyzed it using the PLS-SEM method through Smart-PLS. The results of the research indicate that perceived convenience and service quality have a significant effect on attitudes, while transaction security only has a significant effect on usage intentions. Furthermore, the mediating effect of attitudes only occurs in the relationship between perceived convenience, service quality, and usage intentions.